Applying Indigenizing Principles of Decolonizing Methodologies in University Classrooms - Louie, Dustin William; Poitras-Pratt, Yvonne; Hanson, Aubrey Jean; Ottmann, Jacqueline (Canadian Journal of Higher Education / Revue canadienne d'enseignement supérieur, 2017)
This case study examines ongoing work to Indigenize education programs at one Canadian university. The history of the academy in Canada has been dominated by Western epistemologies, which have devalued Indigenous ways of knowing and set the grounds for continued marginalization of Indigenous students, communities, cultures, and histories. We argue that institutions of higher learning need to move away from the myopic lens used to view education and implement Indigenizing strategies in order to counteract the systemic monopolization of knowledge and communication. Faculties of education are taking a leading role in Canadian universities by hiring Indigenous scholars and incorporating Indigenous ways of knowing into teacher education courses. Inspired by the 25 Indigenous principles outlined by Maōri scholar Linda Tuhiwai Smith (2012), four Indigenous faculty members from Western Canada document effective decolonizing practices for classroom experience, interaction, and learning that reflect Indigenous values and orientations within their teaching practices.